1987
DOI: 10.1128/aac.31.6.860
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenously administered ciprofloxacin in patients with various degrees of renal function

Abstract: m2). Because of the observed variation in ciprofloxacin half-life in our anephric volunteers, we also recommend that a schedule of administration every 12 h be maintained, even for patients without urine output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 8 publications
1
36
0
1
Order By: Relevance
“…Normally, 30 to 50% of ciprofloxacin is eliminated through hepatic metabolism and biliary excretion. It has been demonstrated that ciprofloxacin CL S does not always correlate well with creatinine clearance (1,6,11,23,26), and it has been suggested that increases in biliary clearance may effectively compensate for a reduction in renal clearance in patients with renal impairment (12,13,14). In the present study, 5 of the 10 patients receiving ciprofloxacin also had severe hepatic impairment.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Normally, 30 to 50% of ciprofloxacin is eliminated through hepatic metabolism and biliary excretion. It has been demonstrated that ciprofloxacin CL S does not always correlate well with creatinine clearance (1,6,11,23,26), and it has been suggested that increases in biliary clearance may effectively compensate for a reduction in renal clearance in patients with renal impairment (12,13,14). In the present study, 5 of the 10 patients receiving ciprofloxacin also had severe hepatic impairment.…”
mentioning
confidence: 52%
“…Total systemic clearance of ciprofloxacin in this patient population was noted to be highly variable, ranging from 0.34 to 1.70 ml/min/kg (compared to 7 to 8 ml/min/kg in patients with normal renal function) (1,6,11,23,26). This could possibly be attributed to variability in nonrenal mechanisms of drug clearance, as well as variations in the efficiency of clearance via CRRT.…”
mentioning
confidence: 95%
“…In addition, CIP is reported to be the main metabolite of enrofloxacin, another antibacterial quinolone used in veterinary medicine (22). Although most of the pharmacokinetic work with this drug has been focused on humans (6,9,10,16), some studies have also been carried out on animals, such as rats, monkeys (20,21), rabbits (2,3), pigs, calves (14), horses (28), fish (13), and dogs (1,26). These studies indicate that CIP exhibits favourable pharmacokinetic properties: it is quickly distributed, and its apparent volume of distribution, greater than 1.0 1/kg in all the species studied, suggests substantial tissue penetration.…”
Section: Introductionmentioning
confidence: 99%
“…The drug exhibits linear pharmacokinetics at doses of 25 to 400 mg. In contrast to those from healthy volunteers (6,9,12,15,22,32) or stable patients with renal insufficiency (9,32), very few usable data (10,16,20,23,33) have been published for any target populations. Also, there are no pharmacokinetic data derived from patients receiving doses of 400 mg every 8 h, a regimen currently being studied for severe infections.…”
mentioning
confidence: 99%